Thermal and mechanical analysis of thermal break with end-plate for attached steel structures. (15th January 2017) - Ben Larbi, A.; Couchaux, M.; Bouchair, A.
Highlights: Solutions for Nearly Zero Energy steel Buildings. Thermal break for attached steel structures with end-plate. It reduces by 20–65% the thermal bridge at the attached steel structure. Mechanical tests show good ultimate behaviour with sufficient ductility of the system. The cyclic loading behaviour of the connection is quite similar to that obtained under monotonic loading. Abstract: The thermal and mechanical performances of a simple thermal break are analysed. This thermal break can be used with external steel structures such as balconies and passageways attached on a concrete facade with external thermal insulation. The thermal barrier effect is obtained by a PVC and an acoustic insulation plates inserted between the end-plates of the attached steel beams and the support (floor slab, concrete wall). The thermal performances of the selected solutions were evaluated by numerical simulation. It shows that this simple solution reduces by up to 65% the thermal bridge at the attached steel beams connections. Besides, a parametric analysis showed that the reduction ratio depends on the configuration of thermal break (with or without additional thermal insulation around the steel beams at the connection), the thickness of PVC plate, the material of fastening systems (carbon steel or stainless steel) and the thickness of the facade thermal insulation. As deformable layers are used under the end-plates, the thermal break can be considered as unconventional steel connection with mechanical performances to be investigated. Thus, experimental program including static and cyclic tests is performed on various configurations of connections with thermal breaks to evaluate their mechanical behaviour considering the stiffness and the resistance. The results show that the solution of simple thermal break is efficient mainly for connections with extended end-plates.